Estudo do sono e de associação de polimorfismos do gene PER3 em uma população de pacientes portadores de transtorno afetivo bipolar - Paulo Marcos Brasil Rocha (2014)
Bipolar disorder (BD) is a chronic and recurrent psychiatric condition which can lead to poorer social functioning and quality of life. A great amount of evidences from several lines of genetic research have confirmed that BD is highly heritable. Thus, vulnerability to BD would be linked to the permanent interaction between genetic and environmental factors. The role of sleep and circadian disturbances in BD has been recognized as an essential aspect of the illness, as they may occur both in mania and depression. In the present manuscript sleep evaluation as well as a case-control genetic association study was carried out to test the relationship between the Per3 gene and BD. We specifically compared sleep quality and the Per3 gene polymorphisms between euthymic bipolar disorder patients and controls. A total of 209 BD patients fulfilling criteria for euthymia and 213 controls joined the study. Sleep quality was accessed by the Pittsburgh Sleep Quality Index (PSQI) which distinguishes good and poor sleepers by means of the PSQI global score. Genotyping was performed with the Real-Time Polymerase Chain Reaction technique. Statistical analysis was performed with a significance level of 5%. The two groups were significantly different in relation to sleep quality assessed by the PSQI, as a large amount of BD patients reported poor sleep quality despite the fact that they were euthymic. After multivariate analyses controlling for clinical and demographic variables between cases and controls, association remained significant between BD and poor sleep quality assessed by the PSQI. Allelic and genotypic distribution analyses of the Per3 polymorphisms between the two groups revealed a significant association between the rs707467 polymorphism and BD, although the association did not reach statistical significance after correction for multiple tests. The high prevalence of poor sleep quality in BD hypothesis was confirmed. The association between poor sleep quality and BD remained significant after multivariate analysis. The lack of association found between the Per3 polymorphisms and BD in this study raise questions about the possible role for the Per3 gene in the neurobiology of BD, since previous studies have shown mixed results. More studies with larger samples are needed to better understand whether the Per3 gene would represent a vulnerability trait for BD.